IMPACT OF MANAGERIAL FACTORS ON EXPORT PERFORMANCE OF EXPORT FIRMS (Singaporean Journal of Business Economics and Management, 2013)
In this research has investigated six factors including International experience, foreign language skills, time spent abroad, international business knowledge, perceived export stimuli, perceived export barriers. To collect data related to these factors distributed researcher made questionnaire among the managers of exporter in Rasht and then were analyzed by SPSS software. Result show that there is significant relationship between six factors and export performance of companies.